PENGARUH BUDAYA ORGANISASI, MEDIA SOSIAL, DAN TEMAN SEBAYA TERHADAP SPRITUALITAS SISWA - Ira Damayanti Hasibuan; Muhammad Fadhli (SKILLS : Jurnal Riset dan Studi Manajemen Pendidikan Islam, 2026)
This study aims to analyze the influence of organizational culture, social media, and peer relationships on the spirituality of twelfth-grade students at MAN 1 Medan. The study employs a quantitative approach with an explanatory design and utilizes Partial Least Square–Structural Equation Modeling (PLS-SEM) for data analysis. The research sample consists of 240 students selected through a simple random sampling technique from a population of 601 students. Data were collected using a Likert-scale questionnaire that has been tested for validity and reliability. The results indicate that organizational culture, social media, and peer relationships have a positive and significant effect on students’ spirituality, both partially and simultaneously. Organizational culture emerges as the most dominant variable influencing students’ spirituality, with discipline identified as the strongest indicator. The coefficient of determination (R-square) value of 0.527 indicates that these three variables explain 52.7% of the variance in students’ spirituality. These findings confirm that students’ spirituality is shaped by the interaction between formal environmental factors (school) and informal factors (social media and peer groups). The implications of this study highlight the importance of strengthening school culture based on religious values and discipline, managing social media use wisely, and fostering positive peer environments. This research contributes theoretically to the development of spirituality-based Islamic education studies and provides practical insights for schools in designing character-building strategies in the digital era.